How does RASTI change with sound reinforcement systems in churches? - A. Carvalho (1999)
The Rapid Speech Transmission Index (RASTI) was measured in 31 Catholic churches in Portugal built in the last 11 centuries. Four receiver locations were used in each church, with and without the use of sound reinforcement systems (SRS) from the altar area. The loudspeaker arrangement commonly present in the churches tested was the distributed line source system (but with no signal-delayed), which is the standard in Portugal. This paper concentrates on the RASTI values within churches (with SRS) and on their differences with and without the SRS on. The results are graphed and analyzed using correlation procedures and statistical modeling. The mean RASTI values without SRS varied from 0.22 to 0.56 while the ones with SRS changed from 0.26 to 0.66. Regarding the RASTI improvement by the use of SRS, a R2 of 0.55 was found for its relationship with the Distance to the Altar. It was detected that only for distances greater than about 10 m from the altar area is the SRS useful in increasing the RASTI values. In summary, it was found that the SRS systems used in Portuguese churches induce an average increase of 7% in the RASTI values or about 0.03 in their absolute value.